IMPLEMENTATION OF PT BERAU COAL'S CORPORATE SOCIAL RESPONSIBILITY AND GREEN ACCOUNTING FOR SUSTAINABLE DEVELOPMENT - Darmono, Darmono; Ramdan, Ramdan (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
This research aims to analyze the use of Corporate Social Responsibility (CSR) and Green Accounting at PT Berau Coal towards sustainable development. The type of research used in this research is research. This research uses secondary data, obtained from the analysis of PT Berau Coal's annual report. The data analysis technique used in this research is the Miles and Huberman Model data analysis technique. The results of this research indicate that PT. Berau Coal has played a quite good role in efforts to realize sustainable development. PT. Berau Coal increases economic growth by providing substantial regional income and helping communities around the mine to become independent by providing financial assistance, coaching and facilities related to independent economic businesses such as assistance to MSMEs. The role of social activities is to provide educational assistance to the community appropriately and effectively. For environmental contributions, PT. Berau Coal tries to help build independent communities, especially in the agricultural and plantation sectors by providing land, seeds and guidance related to agriculture and plantations. PT. Berau Coal has also implemented green accounting in the form of reporting environmental costs such as environmental prevention costs and internal failure costs in the annual report for each period.